Generic characterisation of civil engineering research article abstracts - Budsaba Kanoksilapatham, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
English is increasingly used in advanced education. Among academic writing types, abstracts are one of the pivotal genres of communication among scholars from multiple disciplines. Nevertheless,non-English speaking scholars find the task of writing successful abstracts daunting and challenging. As a consequence, they might not be able to fully participate in their respective academia. To help these scholars disseminate their research findings,this study has the objectives of:1) identifying the structural organisation commonly followed in civil engineering abstracts and (2) identifying a set of linguistic features commonly associated with a particular type of information presented in the abstracts. To accomplish these objectives, a data set of 60 English abstracts belonging to civil research articles systematically selected from the top journals in civil engineering was compiled and analysed with reference to Swales’ genre analysis. The subsequent analysis reveals a typical pattern of how information presented in the abstracts is organised. Furthermore, each information type was linguistically characterised by a cluster of linguistic features that frequently co-exist. These findings capture what constitutes an appropriate academic style of writing in civil engineering abstracts. The study thus helps form a pedagogical model viable and useful for civil engineering scholars to develop strategies in response to the rigorous writing demands of academia. A better understanding of how research article abstracts are constructed can enhance not only their writing skills to conform to the expectations of the target discourse community, but also the chance of success in their respective fields.